Tools and tips of thriving with vegetables: radio IITA vegetable farmers outreach - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
This hands-on training equips vegetable farmers with the practical tools and knowledge they need to boost productivity, reduce losses, and increase profits. The sessions combine field demonstrations, expert insights, and real-life farmer experiences to support sustainable vegetable production. The sessions combine field demonstrations, expert insights, and real-life farmer experiences to support sustainable vegetable production, profits.